Census Valachorum in mid-16th century upper Hungary - Diaconescu, Marius (Balcanica Posnaniensia. Acta et studia, 2015)
The Vlachs in mid-16th century Upper Hungary had different obligations than all other subjects of the feudal estate. The sum of all fiscal obligations of the Vlachs is summarized in the census of the Muráň castle estate, which always designates it under the name “<span style="font-family: 'Times New Roman','serif'; font-size: 12pt; mso-fareast-font-family: TimesNewRomanPS-ItalicMT; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">census Valachorum”, a phrase that includes the delivery of sheep, lambs, quarks, or pieces of harness for horses. Their main obligation consisted in a number of sheep, lambs, and goats according to the size of their flock, which they delivered around the Pentecost. Another obligation typical of the Vlachs was the bellows cheese. For every flock was due a harness (<span style="font-family: 'Times New Roman','serif'; font-size: 12pt; mso-fareast-font-family: TimesNewRomanPS-ItalicMT; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">cinctorium), named at times after its Hungarian equivalent, <span style="font-family: 'Times New Roman','serif'; font-size: 12pt; mso-fareast-font-family: TimesNewRomanPS-ItalicMT; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">heveder. If this harness is common to a number of the feudal estates, on the Muráň castle estate it was supplemented by a wool fabric, called in Hungarian <span style="font-family: 'Times New Roman','serif'; font-size: 12pt; mso-fareast-font-family: TimesNewRomanPS-ItalicMT; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">nemez, and in Latin <span style="font-family: 'Times New Roman','serif'; font-size: 12pt; mso-fareast-font-family: TimesNewRomanPS-ItalicMT; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">subsellium, probably because it was used as felt padding for the horseback, under the saddle.